Incidence and risk factors of dementia and the primary subtypes in northern rural China. Issue 13 (2nd April 2021) - Gu, Xingzhong; Shi, Zhihong; Liu, Shuai; Guan, Yalin; Lu, Hui; Zhang, Ying; Zhang, Meilin; Liu, Shuling; Yue, Wei; Wu, Hao; Wang, Xiaodan; Zhang, Yajing; et al.
Abstract : Abstract: This study was carried out to estimate the incidence and to determine socio-demographic risk factors for dementia among individuals residing in rural northern China. The current prospective, population-based study was conducted between 2011 and 2016. Follow-up interviews were conducted annually from 2014 to 2016. The study involved 1511 dementia-free individuals aged 60 years or above from rural China. Standard criteria were used to make diagnoses for dementia and Alzheimer disease (AD). At least one follow up survey was completed with 1181 study participants. At the 5-year follow-up, 127 individuals had developed dementia, 75 had developed AD, and 32 had developed vascular dementia (VaD). With a total of 5649.2 risk years for the sample, the estimated incidence rates per 1000 person-years were 22.48 (95% CI: 18.62, 26.35) for dementia and 13.28 (95% CI: 10.29, 16.26) for AD. Incidence rates for dementia and AD increased with age across the 10-year age groups. Poor education (illiteracy) was an independent risk factor for both AD and VaD. Being engaged in social activities was an independent protective factor for VaD. The incidence of dementia in rural China was found to be higher than previously reported. Incidence of dementia increased with age, and AD was the most frequent type of dementia. Poor education was associated with a higher risk of VaD and AD. Engagement in social activities was an independent protective factor for VaD.